SISTEM PAKAR UNTUK DIAGNOSA PENYAKIT ANAK DENGAN METODE CASE-BASED REASONING DENGAN ALGORITMA SIMILARITY JACCARD PADA PUSKESMAS HALMAHERA SEMARANG - Wibisono,S.Kom, M.Cs, Setyawan; Trisulo, Didik (Information Technology and Telematics, 2019)
Abstract -Health is the most valuable thing for humans, because anyone is prone to health problems. Children are very susceptible to germs and sensitivity to the symptoms of an illness is their own fear for parents. Parents are laymen in the world of health. So that in this case in the health sector more requires an expert who can make it easier to diagnose a disease more quickly so that parents can take precautions early if it can take longer if you consult with a specialist. The purpose of this study was to design and expert systems for diagnosing pediatric diseases using the cased-based reasoning method with a similarity jaccard algorithm at the Halmahera Health Center Semarang so as to help provide information about the diagnosis of pediatric disease at the web-based Halmahera Semarang Puskesmas.Designing expert systems for diagnosing pediatric diseases using the cased-based reasoning method with the similarity jaccard algorithm at the Halmahera Semarang Community Health Center was created using tools such as PHP, Xampp, Bootstrap.The results of the expert system for diagnosing pediatric disease using the cased-based reasoning method with the similarity jaccard algorithm at the Halmahera Health Center Semarang can help provide information about the diagnosis of pediatric disease at the Halmahera Health Center Semarang.